A global summary of seafloor topography influenced by internal-wave-induced turbulent water mixing - H. van Haren; H. de Haas (Ocean Science)
Turbulent water motions are important for the exchange of momentum, heat, nutrients, and suspended matter, including sediments in the deep sea. The motions occur in a deep sea that is generally stably stratified in density. To maintain ocean–density stratification, an irreversible diapycnal turbulent transport is needed. The geological shape and texture of marine topography are important for water mixing, as most deep-sea turbulence is generated via internal waves breaking at sloping seafloors. For example, slopes of semidiurnal internal tidal characteristics can “critically” match the mean seafloor slope. In this paper, the concept of critical slopes is revisited from a global internal-wave turbulence viewpoint using seafloor topography and moored high-resolution temperature sensor data. Observations suggest that turbulence generation via internal-wave breaking at 5 % ± 1.5 % of all seafloors is sufficient to maintain ocean–density stratification. However, most, >90 %, turbulence contributions are found at supercritical, rather than the more limited critical, slopes measured at 1′ scales that cover about 50 % of seafloors at water depths <2000 m. Internal tides (∼60 %) dominate over near-inertial waves (∼40 %), which is confirmed by comparison of northeastern Atlantic data and eastern Mediterranean data (weak tides) at the same mid-latitude. Seafloor elevation spectra show a wavenumber (k) falloff rate of k−3, which is steeper than what was found previously. The falloff rate is even steeper, resulting in less elevation variance in a 1-order-of-magnitude bandwidth around kT=0.5 cycle km−1. The corresponding length is equivalent to the internal wave excursion length. The reduction in seafloor elevation variance seems to be associated with seafloor erosion by internal wave breaking. The potential robustness of the seafloor and internal wave interaction is discussed.